If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x+3)=10(2x-3)
We simplify the equation to the form, which is simple to understand
5(x+3)=10(2x-3)
Reorder the terms in parentheses
+(+5x+15)=10*(2x-3)
Remove unnecessary parentheses
+5x+15=+10+*(+2x-3+)
Reorder the terms in parentheses
+5x+15=+(+20x-30)
Remove unnecessary parentheses
+5x+15=+20x-30
We move all terms containing x to the left and all other terms to the right.
+5x-20x=-30-15
We simplify left and right side of the equation.
-15x=-45
We divide both sides of the equation by -15 to get x.
x=3
| 3p+16=68 | | 2(5-6X)=142 | | 3(4X+3)=-39 | | 5x-3=3(x+7)+3 | | 23-3x=11 | | -23=n-4 | | 7(7+2X)=35 | | 4(x+1)=3(2x+2) | | 8x^2+52x+7=0 | | 6(x-8)+8=-40 | | 4m+5=-11 | | 26=6a-10 | | 2=a+12 | | 13x-2=180 | | (x+2)(x-1)=2x | | 4x^5+28x^4+49x^3=0 | | 5(3-2x)+4=3 | | 9x^3-9x^2-4x+4=0 | | kx^2+4x+k=0 | | b-5=-15 | | 2x+7x=9 | | 2x^2-3x+36=11+17x-2x^2 | | B-19=28 | | 5(1+y)-3y=3 | | f(4)=45,000(1+1.67/12)12(4) | | 26=13+x+9 | | 9-2n=3(n+2) | | m=-.25(2,1) | | 36u^2=9 | | 36u=9 | | p=(2a-1)+(a+4)+(2a-1)+(6a-3) | | 34-7x=-57 |